Money as a Unit of Account - Doepke, Matthias; Schneider, Martin (Econometrica, 2017)
We develop a theory that rationalizes the use of a dominant unit of account in an economy. Agents enter into non-contingent contracts with a variety of business partners. Trade unfolds sequentially in credit chains and is subject to random matching. By using a dominant unit of account, agents can lower their exposure to relative price risk, avoid costly default, and create more total surplus. We discuss conditions under which it is optimal to adopt circulating government paper as the dominant unit of account, and the optimal choice of ?currency areas? when there is variation in the intensity of trade within and across regions.